2017
DOI: 10.1111/1468-5973.12195
|View full text |Cite
|
Sign up to set email alerts
|

Informing crisis alerts using social media: Best practices and proof of concept

Abstract: Social media has become an integrated part of human communication, both as a means to establish and maintain social relationships, and as a means of sharing and co-creating information. Social media comes with an array of possibilities for individuals as well as organizations, corporations, and authorities. Within the field of crisis communication, social media possibilities such as online sharing and social networking have had an impact on the way crisis information is disseminated and updated. This paper add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 45 publications
1
29
0
1
Order By: Relevance
“…To date, research on terse messaging in risk communication has focused largely on best practices for social media platforms, such as Twitter (Bean et al, ; Brynielsson et al, ), but scholarship evaluating WEA messages, or text messages more generally, is increasing. Wireless Emergency Alert research has investigated geotargeting delivery mechanisms (Gunduzhan, Doshi, & Benmohamed, ) and how message style and content, including the use of visuals, influence message processing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, research on terse messaging in risk communication has focused largely on best practices for social media platforms, such as Twitter (Bean et al, ; Brynielsson et al, ), but scholarship evaluating WEA messages, or text messages more generally, is increasing. Wireless Emergency Alert research has investigated geotargeting delivery mechanisms (Gunduzhan, Doshi, & Benmohamed, ) and how message style and content, including the use of visuals, influence message processing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, research of Brynielsson et al. () showed that local and regional authorities also can be seen as more trustworthy due to their contextual awareness.…”
Section: Introductionmentioning
confidence: 99%
“…The participants declared that they had not been provided with any education or preset action plans for handling the coronavirus and that all the planning and decision-making began when the infection had already started to become widespread. As mentioned in many studies, timely and proper provision of information is a key factor in controlling critical conditions and minimizing causalities and nancial costs [25].…”
Section: Discussionmentioning
confidence: 99%